The Transitivity Process Patterns and Styles in the Characterization of the Protagonist Character in Phuocâ€™s â€œThe Story of Tam and Camâ€ - Manggala, Simon Arsa (Journal of Language and Literature, 2017)
This paper is based on the notion in Stylistics that the study focuses on language use, the purposes, and the effects (Verdonk, 2002). The data is taken from one of the stories from Vietnam. The story is selected since the plot shares similarities in terms of the plot with the popular Cinderella stories. Therefore, readers are familiar with the plot since Cinderella stories exist in many cultures and languages (Tatar, 1999). The language use is reviewed by utilizing transitivity analysis (Matthiessen & Halliday, 2004) to examine the processes in the characterization since transitivity analysis is a significant analytical tool in accounting ideational perspective systematically (Simpson, 1993). Further, the choice of processes and patterns lead to the discussion on the purposes and effects. The examination on the transitivity analysis shows that the processes employed to characterize the protagonist character are material, mental, relational, verbal, and behavioral processes. The processes might reveal particular significant to the process of characterization. For instance, material processes frequently dominate the characterization of the main character. Thus, the character is mostly characterized by what they do and what happens with them. The other transitivity processes resemble the purpose and effect based on their meanings. Hopefully, this paper might serve an example of how to examine the language patterns in a literary work to further observe the purposes and the effects of the patterns. Keywords: folktale, stylistics, and Transitivity Analysis.